The drift history of the Dharwar Craton and India from 2.37 Ga to 1.01 Ga with refinements for an initial Rodinia configuration - Miller, Scott R.; Meert, Joseph G.; Pivarunas, Anthony F.; Sinha, Anup K.; Pandit, Manoj K.; Mueller, Paul A.; Kamenov, George D. (My University, 2023)
Coupled paleomagnetic and geochronologic data derived from mafic dykes provide valuable records of continental movement. To reconstruct the Proterozoic paleogeographic history of Peninsular India, we report paleomagnetic directions and U-Pb zircon ages from twenty-nine mafic dykes in the Eastern Dharwar Craton near Hyderabad. Paleomagnetic analysis yielded clusters of directional data that correspond to dyke swarms at 2.37 Ga, 2.22 Ga, 2.08 Ga, 1.89–1.86 Ga, 1.79 Ga, and a previously undated dual polarity magnetization. We report new positive baked contact tests for the 2.08 Ga swarm and the 1.89– 1.86 Ga swarm(s), and a new inverse baked contact test for the 2.08 Ga swarm. Our results promote the 2.08 Ga Dharwar Craton paleomagnetic pole (43.1 N, 184.5 E; A95 = 4.3 ) to a reliability score of R = 7 and suggest a position for the Dharwar Craton at 1.79 Ga based on a virtual geomagnetic pole (VGP) at 33.0 N, 347.5 E (a95 = 16.9 , k = 221, N = 2). The new VGP for the Dharwar Craton provides support for the union of the Dharwar, Singhbhum, and Bastar Cratons in the Southern India Block by at least 1.79 Ga. Combined new and published northeast-southwest moderate-steep dual polarity directions from Dharwar Craton dykes define a new paleomagnetic pole at 20.6 N, 233.1 E (A95 = 9.2 , N = 18; R = 5). Two dykes from this group yielded 1.05–1.01 Ga 207Pb/206Pb zircon ages and this range is taken as the age of the new paleomagnetic pole. A comparison of the previously published poles with our new 1.05–1.01 Ga pole shows India shifting from equatorial to higher (southerly) latitudes from 1.08 Ga to 1.01 Ga as a component of Rodinia.
Keywords: Dharwar; India; Rodinia; U-Pb; Paleogeography; Grenville